2004
DOI: 10.1086/381133
|View full text |Cite
|
Sign up to set email alerts
|

Maternally Inherited Aminoglycoside-Induced and Nonsyndromic Deafness Is Associated with the Novel C1494T Mutation in the Mitochondrial 12S rRNA Gene in a Large Chinese Family

Abstract: We report here the characterization of a large Chinese family with maternally transmitted aminoglycoside-induced and nonsyndromic deafness. In the absence of aminoglycosides, some matrilineal relatives in this family exhibited late-onset/progressive deafness, with a wide range of severity and age at onset. Notably, the average age at onset of deafness has changed from 55 years (generation II) to 10 years (generation IV). Clinical data reveal that the administration of aminoglycosides can induce or worsen deafn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
303
1
12

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 333 publications
(319 citation statements)
references
References 48 publications
3
303
1
12
Order By: Relevance
“…Variable estimates on ototoxicity may also be related to patient history. For example, specific mitochondrial defects that are more prevalent in some Asian populations produce extreme sensitivity to aminoglycoside ototoxicity (Usami et al 1998;Zhao et al 2004; for review see Bindu and Reddy 2008). Additionally, previous aminoglycoside treatment has been suggested to effect risk of ototoxicity from subsequent administration based on cumulative drug dose (Chen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Variable estimates on ototoxicity may also be related to patient history. For example, specific mitochondrial defects that are more prevalent in some Asian populations produce extreme sensitivity to aminoglycoside ototoxicity (Usami et al 1998;Zhao et al 2004; for review see Bindu and Reddy 2008). Additionally, previous aminoglycoside treatment has been suggested to effect risk of ototoxicity from subsequent administration based on cumulative drug dose (Chen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The other non-syndromic deafness-associated mtDNA mutations are the 12S rRNA C1494T mutation, the 7472insC, T7505C and T7511C mutations in the tRNA Ser(UCN) gene ,and the T12201C mutation in the tRNA His gene. [13][14][15][16][17] The 12S rRNA mutations impaired mitochondrial translation, leading to deficient respiration. 13,18,19 Mild mitochondrial dysfunctions were observed in cells carrying these mtDNA mutations.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] The 12S rRNA mutations impaired mitochondrial translation, leading to deficient respiration. 13,18,19 Mild mitochondrial dysfunctions were observed in cells carrying these mtDNA mutations. 13,18,19 Therefore, these mtDNA mutations are necessary but insufficient to produce a clinical phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that several mutations in the mitochondrial DNA (mtDNA), including m.1555A>G [3], m.1494C>T [4], m.1095T>C [5], m.837A>G [6], and m.1291T>C [7] may possibly associate with the sensorineural hearing loss, and mutations of m.1555A>G and m.1494C>T at the highly conserved decoding site of 12S rRNA are well documented being associated to either aminoglycoside antibiotics-induced or non-syndromic hearing loss in families with different ethnic backgrounds [3,4,8,9].…”
mentioning
confidence: 99%
“…m.1555A>G mutation in a highly conserved decoding site of the 12S rRNA could associate with both aminoglycoside-induced and non-syndromic hearing loss in families with different ethnic backgrounds, [3,9,17], and the m.1494C>T mutation is also structurally equivalent to the m.1555A>G mutation in the 12SrRNA gene [4,10,11,18].…”
mentioning
confidence: 99%